Trends in insecticide resistance in natural populations of culex quinquefasciatus and its impact on mosquito fitness in Dschang, West Cameroon - Poumachu, Y.; Lontsi-Demano, M.; Zeb, J.; Djoufounna, J.; Djiappi-Tchamen, B.; Hashem, A.; Alajmi, R.A.; Mochie, C.L.; Awono-Ambene, H.P.; Antonio-Nkondjio, C.; Tchuinkam, T.; Abd-Allah, E.F. (2025)
Specific information about the dispersion of Culex quinquefasciatus from Dschang in western Cameroon is scarce, and evidence-based interventions are needed. Common use of larvicides and adulticides conduct to the development of vectors resistance which can lead to deep biological changes, including fitness costs. We assessed the profile of insecticide resistance in field populations of Cx. quiquefasciatus and its potential fitness cost in a lineage selected for deltamethrin and permethrin resistance in the laboratory for two generations. The resistance intensity of the Cx. quinquefasciatus population was moderated when the population was exposed to deltamethrin at 10 × . Preexposure to PBO led to the restoration of full susceptibility to both deltamethrin and permethrin. Compared with that of the control group, female fecundity rates, egg hatchability, and pupation rates were significantly lower in the insecticide exposed groups. Larval development time and adults emergence rates were comparable between insecticide-exposed groups and the control. Insecticide-exposed adults lived longer than control adults did. Our findings suggest that the mechanisms selected for pyrethroid resistance are associated with negative impacts on different life-trait parameters and support the hypothesis that insecticide resistance is related to a high fitness cost.